2015
DOI: 10.1111/jrh.12150
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Asthma Self‐Management in Rural School‐Aged Children: A Randomized Controlled Trial

Abstract: Purpose To test the effects of 2 modes of delivering an asthma educational intervention on health outcomes and asthma self-management in school-aged children who live in rural areas. Methods Longitudinal design with data collected 4 times over 12 months. The target sample was composed of children in grades 2–5 who had a provider diagnosis of asthma. Elementary schools were stratified into high or low socioeconomic status based on student enrollment in the free or reduced-cost lunch program. Schools were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…Asthma control program in Brazil which included training of health professionals and educational interventions for the patients were found to reduce the number of asthma related hospital admissions 20 . Edcuation provided in school asthma class or in asthma day camp also yielded significant reductions in the emergency department and office visits 19 . We found that hospitalizations, emergency room admissions and unscheduled hospital visits were not different between groups but missed school days were significantly lower in education group.…”
Section: Volume 58 • Number 4 Education Intervention In Uncontrolledmentioning
confidence: 95%
See 1 more Smart Citation
“…Asthma control program in Brazil which included training of health professionals and educational interventions for the patients were found to reduce the number of asthma related hospital admissions 20 . Edcuation provided in school asthma class or in asthma day camp also yielded significant reductions in the emergency department and office visits 19 . We found that hospitalizations, emergency room admissions and unscheduled hospital visits were not different between groups but missed school days were significantly lower in education group.…”
Section: Volume 58 • Number 4 Education Intervention In Uncontrolledmentioning
confidence: 95%
“…Most of the studies report reductions in emergency department visits, hospitalizations and overall improvement of asthma control 18,19 . Studies evaluating the effects of education report benefit of education when they evaluate the outcomes on 6th months and 12th months 14,16,[18][19] . We evaluated our outcome measurements 1 and 3 months after intervention.…”
Section: Volume 58 • Number 4 Education Intervention In Uncontrolledmentioning
confidence: 99%
“…These include asthma education delivered via in-school asthma classes or asthma day camps [68]. Interventions focusing on self-management behaviors beyond simple medication compliance have the most potential for improving asthma outcomes in rural children [69].…”
Section: Target Interventions With Improved Asthma Outcomesmentioning
confidence: 99%
“…School‐based accommodations, such as improving access to medications at school and medication administration by school health personnel, can reduce barriers to adherence . A school‐based asthma self‐management program was effective in improving medication adherence compared to an attention control or summer camp self‐management program among rural elementary school children . Home‐based services can increase medication adherence in children with asthma as well .…”
Section: Resultsmentioning
confidence: 99%
“…21 A school-based asthma self-management program was effective in improving medication adherence compared to an attention control or summer camp self-management program among rural elementary school children. 76 Home-based services can increase medication adherence in children with asthma as well. 9,28,74 For example, delivering in-home Multisystemic Therapy adapted for health care for adolescents and their families is associated with improved adherence.…”
Section: Modifiable Community Influencesmentioning
confidence: 99%